Unseen Cinema - The Mechanized Eye: Experiments in Technique and Form Early American Avant-Garde Film 1894-1941 - Beheim, Eric; Hill, Jerome; Kaufmann, Irving (Unseen Cinema, 2005)
The dynamic qualities of motion pictures are explored by cameramen and filmmakers through novel experiments in technique and form. Early cinematographers James White, "Billy" Bitzer, and Frederick Armitage display experimental shooting styles that wowed audiences. Other independent companies further image manipulation through creative staging, editing, and printing, such as a stunning three-screen film that predates Gance's Napoleon. Experiments by photographer Walker Evans, painter Emlen Etting, musician Jerome Hill, and the film collectives Nykino and Artkino record the world in a continual process of flux. A most extreme approach is realized by Henwar Rodakiewicz with "Portrait of a Young Man" (1925-1931), a monumental study of natural and abstract motions. [Cover]